“… give me a lawyer, dawg”: recognizing youthful pleas for advice and support - Wilford, Miko M.; Frazier, Annabelle (Frontiers in Psychology, 2024)
(1) Youth are particularly vulnerable to making suboptimal legal decisions due to added challenges in comprehension, as well as their ongoing neurological development. (2) This fact is especially problematic in our system of pleas, which frequently expects defendants to determine the outcome of their own cases (by accepting or rejecting plea offers). (3) To better ensure that guilty pleas entered by youthful defendants are indeed knowing, intelligent, and voluntary, legal counsel should be mandatory during any and all juvenile criminal proceedings. (4) Further, an additional “translator” (similar to a guardian ad litem), who has specialized training in developmental psychology, should be present to effectively counsel and support youth defendants who might otherwise fail to comprehend the advice of their attorneys (and other court actors).